Expression Analysis and Nuclear Import Study of Full-length Isoforms Importin Î± as 6x Histidin-tagged Fusion Protein on the Intracellular Localization of Recombinant HBV Core Protein - Haryanto, Aris (Universitas Gadjah Mada, 2005)
Isoform importin α molecules play a central role in the classical nuclear import pathway, that occurs throughthe nuclear pore complex (NPC) and typically requires a specific nuclear localization signal (NLS). In this study,it was investigated the role of isoforms importin α in the nuclear import of wild type recombinant hepatitis B viruscore protein (WT rHBc), phosphorylated recombinant HBV core (rHBc) and recombinant HBV core without NLSby co-immunoprecipitation. Four recombinant full-length isoforms importin α as 6x histidin-tagged fusion proteinwere expressed and analysed from expression plasmid vectors Rch1, pHM 1969, pHM 1967 and pHM 1965. Theresults indicated that importin α-1, importin α-3, importin α-4 and importin α-5 can be expressed and isolatedfrom E. coli transformed recombinant DNA plasmid as protein in size around 58-60 kDa. By the nuclear transportstudy shown that isoforms importin α are involved in the nuclear import of WT rHBc, phosphorylated rHBc andrHBc without NLS. It also indicated that they have an important role for nuclear transport of from cytoplasm intothe nucleus.Keywords: NPC, NLS, importin α, importin β, isoforms importin α as 6x histidin-tagged fusion protein, WTrHBc, SV40 Tag, co-immunoprecipitation, westernblotting.